(untitled) (Research, Society and Development, 2022)
Severe combined immunodeficiency (SCID), also known as “bubble boy disease” is a serious defect in cellular and humoral immunity that makes children susceptible to infections. Its diagnosis is made through Neonatal Screening, and in Brazil it is done by the foot test. The treatment is based on the Hematopoietic Stem Cell Treatment (HSCT). Late diagnosis or lack of treatment can cause sequelae or death. Therefore, it is important to implement newborn screening to detect cases of SCID early to avoid irreversible damage. Therefore, the objective of this review is to evaluate neonatal screening for severe combined immunodeficiency and its contribution to carriers. This is a systematic literature review approved by the PROSPERO platform under number CDR42020206341, carried out in MEDLINE, LILACS, in English, Portuguese and Spanish, to be reviewed by two independent authors. Randomized and non-randomized clinical trials, case-control trials, cohort studies and cross-sectional studies in the last five years will be included. After the combined search and application of the inclusion and exclusion criteria, 12 articles were selected to compose the final sample. Neonatal screening is performed by different methods around the world, however, regardless of how it is done, it is possible to note its importance within the health of neonates. The ease of collection contributes to quality care, and the information offered during prenatal care ensures that parents are aware of the need to perform the exam to identify early pathologies that can cause sequelae and even deaths.